(untitled) - Zastrow, Charles; Charles Zastrow (Belmont, CA)
Zastrow's INTRODUCTION TO SOCIAL WORK AND SOCIAL WELFARE: EMPOWERING PEOPLE, 9e International Edition looks at today's society with a realistic view of social problems, and gives you a comprehensive overview of the profession. By presenting positive strategies in the context of the core values, ethics, skills and knowledge base of today's professional social worker, Zastrow motivates you to think about new and realistic ways to solve problems and empower clients. Throughout the book, social problems cases, exhibits, and tables help you apply the concepts and compare and contrast the issues. You can study whenever and wherever you want with the latest technology tools: CengageNOW, an assessment-centered tutorial program that is integrated throughout the book, has interactive components including video segments which depict social work practitioners. Thomson iAudio, which features MP3-ready Audio Lecture Overviews for each chapter and a comprehensive audio glossary of key terms for quick study and review, is also available with this edition. Additionally, a free book-specific website is available to help you succeed. No wonder this is the #1 best- selling book in social work!
Includes bibliographical references and index
Keywords: Social service; Social service; Public welfare